Auditing the risk management process - Pickett, K. H. Spencer (IIA (Institute of Internal Auditors) Ser., 2005)
Risk management is now a part of mainstream corporate life that touches all aspects of every type of organization. Auditors must now focus firmly on risk: risk to the business, risk to the executives, and risk to the stakeholders. Auditing the Risk Management Process incorporates all the latest developments in risk management as it applies to auditors, including the new The Committee of Sponsoring Organizations of the Treadway Commission (COSO) enterprise risk paper.